Strategi Nafkah Berkelanjutan Bagi Rumah Tangga Miskin di Daerah Pesisir - Widodo, Slamet (Makara Human Behavior Studies in Asia, 2011)
This research aims at knowing the factors causing poverty in research area, knowing livelihood strategy by poor households and constructing sustainable livelihood strategy based on the real condition in community. This research is conducted in Kwanyar village, Kwanyar subdistrict of Bangkalan Regency. Data were collected with PRA, FGD method and participative observation involving poor households in research area. Data were analysed with descriptive qualitative method. The result shows that poverty is caused by lack of access to capital, particularly financial capital. This becomes a matter in which fishermen cannot access physical capital as modern catching technology. Livelihood strategy which is conducted by poor household of fishermen consists of economic and social strategies. Economic strategy is conducted with double livelihood pattern, utilizing households worker and migration. Otherwise, social strategy is perfomed with kinship pattern. Traditional welfare organization has also important role for poor households in fulfilling daily needs. In addition, social capital also contributes significantly for livelihood strategy in that area and it becomes one of attentions in arranging sustainable livelihood strategy.